Pengaruh Penambahan Limbah Ekstraksi Buah Kelapa Sawit Terhadap Pembuatan Beton - Halim Kasuma; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The purpose of this research is to utilize the waste of palm oil with investigating the mechanical properties. The waste materials are the result of palm oil extraction. The experiment conducted to investigate the effect of this material over compressive strength, absorption, porosity, and setting time. The content of palm oil waste which added to normal concrete are varieties which are 0%, 2%, 4%, 6%, 8% and 10% of the weight of cement. The porosity test, absorption test and compressive test were performed at ages 7, 14 and 28 days for each test while curing with ordinary water. The results showed that the content of palm oil waste 2%, 4% and 6% decrease the compressive strength. Otherwise the addition of 8% and 10% increase the compressive strength. The absorption and porosity test value increase along with increase the content of palm oil using. The setting time with adding of palm oil waste is faster, rather than normal concrete. In conclusion, utilization of the waste of palm oil for concrete mixture can be done.Keyword: Concrete, Waste of Palm Oil, Extraction, Compressive strength, Porosity, Setting time